A companion to Catholicism and recusancy in Britain and Ireland: from Reformation to emancipation - Scully, Robert E.; Ellis, Angela (Brill's companions to the Christian tradition, 2022)
"This book is an edited collection of nineteen essays written by a range of experts and some newer scholars in the areas of early modern British and Irish history and religion. In addition to English Catholicism, developments in Ireland, Scotland, and Wales, as well as ongoing connections and interactions with Continental Catholicism, are well incorporated throughout the volume"--